Prevalence and factors associated with major depression among female sex workers in post-conflict Gulu district: a cross-sectional study - Simple Ouma; Nazarius Mbona Tumwesigye; Rawlance Ndejjo; Catherine Abbo (BMC, 2021)
Abstract Background Female sex workers operating in conflict-affected settings could be at a much greater risk of major depression. However, the epidemiology of major depression in this population remains understudied. We aimed to determine the prevalence and the factors associated with major depression among FSWs in the post-conflict Gulu district in Northern Uganda. Methods We conducted a cross-sectional study among 300 randomly selected adult female sex workers in Gulu. We utilized a pre-tested semi-structured questionnaire, embedded with MINI 7.0.0, to gather information from each participant through face-to-face interviews. We collected data on socio-demographic characteristics, sex-work-related characteristics, alcohol and drug use, HIV status, and major depression. Then, data were entered into EPI INFO 7 and analyzed using logistic regression with the aid of STATA 14.0. Results The mean age (SD) of the study participants was 26.4 (± 6) years, 57.7% attained primary education, 51.7% never married, and 42.1% were living with HIV. The prevalence of major depression among FSWs in the district was 47.7%. In addition, the majority of the FSWs with major depression (91.0%) had either severe (50.4%) or moderate (40.6%) depressive symptoms. Independently, life stress (adjusted OR = 10.8, 95%CI: 5.67-20.57), living with HIV (adjusted OR = 2.25, 95%CI: 1.25-4.05), verbal abuse (adjusted OR = 2.27, 95%CI: 1.27-4.08), and older age (adjusted OR = 1.06, 95%CI: 1.01-1.12) all showed positive associations with major depression. Conversely, provision of sexual services from clients' homes (adjusted OR = 0.50, 95%CI: 0.25-0.97), use of a non-barrier modern family planning method (adjusted OR = 0.44, 95%CI: 0.24-0.82), and daily intake of alcohol (adjusted OR = 0.50, 95%CI: 0.28-0.88) all showed negative associations with major depression. Conclusions There is a high prevalence of major depression among female sex workers in post-conflict Gulu. The high prevalence of major depression underscores the need for government and development partners to urgently and adequately address the mental health needs of female sex workers.